Lost bones: differential diagnosis of acro-osteolysis seen by the pediatric rheumatologist - Elizaveta Limenis; Jennifer Stimec; Peter Kannu; Ronald M. Laxer (BMC, 2021)
Abstract Introduction Acro-osteolysis is a radiographic finding which refers to bone resorption of the distal phalanges. Acro-osteolysis is associated with various conditions and its presence should prompt the clinician to search for the underlying etiology. The aim of this review is to discuss disorders with which acro-osteolysis is associated and their distinguishing features, with a focus on the pediatric population. Methods A targeted literature review was performed using the term "acro-osteolysis" in combination with other key terms. The primary search results were supplemented using reference citations. Articles published prior to the year 2000 were included if they described additional associations not encountered in the more recent literature. Results Genetic disorders (particularly primary hypertrophic osteoarthropathy and skeletal dysplasias) and rheumatic diseases (particularly psoriatic arthritis and systemic sclerosis) are the most frequently encountered conditions associated with acro-osteolysis in children. Hyperparathyroidism, neuropathy, local trauma and thermal injury, and spinal dysraphism should also be included in the differential diagnosis. Conclusion Although acro-osteolysis is uncommon, its presence should prompt the clinician to consider a differential diagnosis based on clinical and radiographic features.